Modelling professional cyclists' careers with UCI points - Filipas, L.; Giorgi, H.; La Torre, A.; Menaspa, P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Retrospective analysis of road cycling race results can support long-term planning and be useful in the development of peak performances (Schumacher et al. 2006). To date, it is unclear when successful General Classification (GC) contenders achieve their first top 5 (T5) or top 10 (T10) result in the context of their cycling career. The main aim of this longitudinal analysis was to compare the careers of GC contenders before and after achieving a T5 versus T10 result using the Union Cycliste Internationale (UCI) point scoring system. Methods. Professional cyclists who achieved their first T10 GC result in a Grand Tour (Giro, Tour and Vuelta) between 2009 and 2014 were included in the analysis. This time frame was selected because it followed the introduction of the biological passport in 2008 and allowed for the inclusion of the UCI points scored during the year following each cyclist`s first T10 performance. A period of 5 years, which included 3 years before and 1 year after the year of the first T5 or T10, was considered for the analysis. UCI points are available online and were collected at the end of 2015. Descriptive statistics were used to report demographic information, and t-tests were used to compare annual points aggregates, previous GT history and number of seasons as a pro cyclist in T5 and T10. Data were reported as mean±SD, and alpha was set to <0.05 a priori for differences. Results: Riders achieved their first GC result at 28.5±5.2 and 27±3.8 years of age for T5 and T10, respectively. T5 group consisted of 71% Europeans, 18% South Americans and 12% North Americans; T10 group consisted of 83% Europeans, 9% South Americans and 9% North Americans. Riders scored more points in the season of a T5 finish (192±73) than a T10 (146±77) (p<0.05). For both T5 and T10 the seasonal points were significantly lower in each previous seasons (p<0.05). There were no differences in the number of GT participations (5.2±3.9 and 3.5±3.0 for T5 and T10, respectively), nor in the number of seasons as a pro cyclist (5.8±3.7 and 4.7±2.9 for T5 and T10, respectively). Discussion: Most of the subjects were European, which is unsurprising given that all the races and most of the teams were European. The average age at which cyclists achieved their first T5/10 result is similar to other endurance sports (Allen & Hopkins, 2015). Professional cyclists usually ride 3 Grand Tours before reaching a T10 finish. Interestingly, the seasonal progression to a top result was not gradual. After achieving the top result, riders maintained a stable level of performance and accumulated a similar number of UCI points during the following season.